(untitled) (Journal of Statistical Research, 2025)
Trimmed mean has been considered a robust estimator of location parameters over the last five decades. The issue of outlier detection has been considered using analytical and graphical statistical tools. This article proposes a graphical device based on the trimmed mean to check whether data has any outliers or not, and in the presence of outliers, the proposed graphical device enables the estimation of the proportion of the outliers as well. The extension of the methodology to the high dimensional data is also outlined. Furthermore, the proposed visualization toolkit is implemented on economic data and gives us an idea of the presence/absence of influential observations/outliers. Journal of Statistical Research 2025, Vol. 59, No. 1, pp. 9-30